Neoadjuvant chemotherapy and nivolumab in resectable non-small-cell lung cancer (NADIM): an open-label, multicentre, single-arm, phase 2 trial. Issue 11 (November 2020) - Provencio, Mariano; Nadal, Ernest; Insa, Amelia; García-Campelo, María Rosario; Casal-Rubio, Joaquín; Dómine, Manuel; Majem, Margarita; Rodríguez-Abreu, Delvys; Martínez-Martí, Alex; De Castro Carpeño, Javier; Cobo, Manuel; López Vivanco, Guillermo; et al.
Summary: Background: Non-small-cell lung cancer (NSCLC) is terminal in most patients with locally advanced stage disease. We aimed to assess the antitumour activity and safety of neoadjuvant chemoimmunotherapy for resectable stage IIIA NSCLC. Methods: This was an open-label, multicentre, single-arm phase 2 trial done at 18 hospitals in Spain. Eligible patients were aged 18 years or older with histologically or cytologically documented treatment-naive American Joint Committee on Cancer-defined stage IIIA NSCLC that was deemed locally to be surgically resectable by a multidisciplinary clinical team, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients received neoadjuvant treatment with intravenous paclitaxel (200 mg/m 2 ) and carboplatin (area under curve 6; 6 mg/mL per min) plus nivolumab (360 mg) on day 1 of each 21-day cycle, for three cycles before surgical resection, followed by adjuvant intravenous nivolumab monotherapy for 1 year (240 mg every 2 weeks for 4 months, followed by 480 mg every 4 weeks for 8 months). The primary endpoint was progression-free survival at 24 months, assessed in the modified intention-to-treat population, which included all patients who received neoadjuvant treatment, and in the per-protocol population, which included all patients who had tumour resection and received at least one cycle of adjuvant treatment. Safety was assessed in the modified intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT03081689, and is ongoing but no longer recruiting patients. Findings: Between April 26, 2017, and Aug 25, 2018, we screened 51 patients for eligibility, of whom 46 patients were enrolled and received neoadjuvant treatment. At the time of data cutoff (Jan 31, 2020), the median duration of follow-up was 24·0 months (IQR 21·4–28·1) and 35 of 41 patients who had tumour resection were progression free. At 24 months, progression-free survival was 77·1% (95% CI 59·9–87·7). 43 (93%) of 46 patients had treatment-related adverse events during neoadjuvant treatment, and 14 (30%) had treatment-related adverse events of grade 3 or worse; however, none of the adverse events were associated with surgery delays or deaths. The most common grade 3 or worse treatment-related adverse events were increased lipase (three [7%]) and febrile neutropenia (three [7%]). Interpretation: Our results support the addition of neoadjuvant nivolumab to platinum-based chemotherapy in patients with resectable stage IIIA NSCLC. Neoadjuvant chemoimmunotherapy could change the perception of locally advanced lung cancer as a potentially lethal disease to one that is curable. Funding: Bristol-Myers Squibb, Instituto de Salud Carlos III, European Union's Horizon 2020 research and innovation programme.